Private lives of the ancient mariner : Coleridge and his children - Lefebure, Molly (The Lutterworth Press, 2013)
A fascinating new study of Samuel Taylor Coleridge, The Private Lives of the Ancient Mariner illuminates the poet's deeply troubled personality and stormy personal life through a highly original study of his relationships. In her last published work the celebrated Coleridgean, Molly Lefebure, provides profound psychological insights into Coleridge through a meticulous study of his domestic life, drawing upon a vast and unique body of knowledge gained from a lifetime's study of the poet, and making skilful use of the letters, poems and biographies of the man himself and his family and friends.